Determinants of entrepreneurial intentions of university students in selected post-communist countries in Europe: investigating cross-cultural differences - Tomal, Mateusz; Szromnik, Andrzej (Journal of Business Economics and Management, 2022)
Main goal of this study is to explore the entrepreneurial intentions of students in selected European post-communist states. The second purpose of the research is to learn about those determinants which, according to the respondents themselves, are essential for the emergence of entrepreneurial intentions. In short, the results of hierarchical multiple OLS regression indicated that the most important factor influencing the entrepreneurial intentions of the surveyed students was entrepreneurial self-efficacy. Moreover, based on estimates of the final regression model, it was identified that dummy variables concerning the respondents’ country significantly moderate the relationship between entrepreneurial self-efficacy and the dependent variable. It can be noted that the strength of the impact of the above-mentioned regressor is closely related to the values of Hofstede’s dimensions of national culture. The obtained results were fully confirmed using an alternative research method, i.e. the ordered logit model. In the second stage of the study, it was revealed that the desire to be independent is the most frequently cited factor motivating the respondents to start their own business. Moreover, using the multiple marginal independence (MMI) testing method, it was found that student responses differ significantly among the examined countries, except for two cases, i.e. Russia and Latvia, and the Czech Republic and Slovakia. First published online 30 November 2021